2017
DOI: 10.1016/j.foodres.2017.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of solubilised carbon dioxide at low partial pressure on crystallisation behaviour, microstructure and texture of anhydrous milk fat

Abstract: The crystallisation and melting behaviour, fat polymorphs, microstructure and texture of anhydrous milk fat (AMF) was investigated in the presence of dissolved CO (0-2000ppm) under two crystallising conditions (non-isothermal versus isothermal). CO was found to induce higher onset crystallisation temperature during cooling from 35 to 5°C at 0.5°Cmin. X-ray scattering analysis showed that, in the presence of dissolved CO this rapid crystallisation caused the formation of unstable, α polymorph fat crystals. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 29 publications
(35 reference statements)
0
10
0
Order By: Relevance
“…Influence of carbon dioxide (CO 2 ) on crystallization and bulk properties of milkfat has been studied recently (Truong, Palmer, Bansal, & Bhandari, 2017;Truong, Palmer, Bansal, Bhandari, & Hub, 2018). Mechanisms and kinetics of nucleation and crystal growth can be influenced by dissolved or suspended entities present in the fat.…”
Section: Incorporation Of Carbon Dioxidementioning
confidence: 99%
See 1 more Smart Citation
“…Influence of carbon dioxide (CO 2 ) on crystallization and bulk properties of milkfat has been studied recently (Truong, Palmer, Bansal, & Bhandari, 2017;Truong, Palmer, Bansal, Bhandari, & Hub, 2018). Mechanisms and kinetics of nucleation and crystal growth can be influenced by dissolved or suspended entities present in the fat.…”
Section: Incorporation Of Carbon Dioxidementioning
confidence: 99%
“…Due to rapid crystallization, unstable species of α-form crystals were formed together with β′ and β polymorphs whereas non-treated AMF exhibited only β′ and β fat polymorphs. Increasing dissolved CO 2 concentration further to 2000 ppm was associated with relatively smaller sized crystals with two-to threefold increase in crystal numbers and solid fat content during isothermal crystallization at 28 °C for 20 min (Truong et al, 2017). Carbonation in cream and butter has also been investigated to study its effect on microbial stability, flavour and keeping quality (Hunziker, 1924;Prucha, Brannon, & Ruehe, 1925).…”
Section: Incorporation Of Carbon Dioxidementioning
confidence: 99%
“…Our previous research demonstrated the effect of dissolved CO 2 at low pressure on crystallisation, microstructural and textural properties of AMF (Truong et al, 2017a). This study has shown that, depending on crystallisation conditions, the effects of CO 2 mirror those M A N U S C R I P T…”
Section: Discussionmentioning
confidence: 64%
“…In a previous study, we demonstrated that infused carbon dioxide (CO 2 ) can also be used to modulate crystallisation behaviour, microstructure and texture of AMF (Truong, Palmer, Bansal, & Bhandari, 2017a) and that some of these effects are similar to those seen in sonocrystallisation. That is, dissolved CO 2 enhanced crystallinity, accelerated crystal nucleation and induced a larger number of smaller crystals than observed in untreated AMF.…”
Section: A C C E P T E Dmentioning
confidence: 96%
See 1 more Smart Citation